Why a jetliner vibrates during takeoff: simulating air oscillations under the wing. (2016) - Raczynski, Stanislaw
Using a gas flow simulation tool, the oscillations of the air around the wing are analysed. It is pointed out that the flow behind and below the wing oscillates with sub- or low acoustic frequencies. Such external excitation may enter into resonance with the natural vibration frequencies of the wings and fuselage, which can produce a dangerous effect. The point of the article is that the fuselage vibration on takeoff depends mainly on what happens in the surrounding air flow. The tool used in flow simulation is equipped with the frequency analysis procedure that shows the spectrum of the oscillations (pressure) in selected points. This permits to identify the main frequencies and amplitudes of the oscillation. The results show that there are several sub-acoustic frequencies (infrasound) that may produce oscillating forces of up to several hundreds of kilograms per square meter of the wing. The topic is closely related to the safety issues.